Optical and structural analysis of bulk ZnO samples undoped and rare earth doped by ion implantation - Monteiro, T. (2006)
ZnO, with its high energy bandgap of ∼3.3 eV, has been in the last years one of the most studied materials. The main driving force of the research performed in this oxide semiconductor is directly related to the ability and potentialities of ZnO for optoelectronic and spintronic applications. In the domain of optoelectronics, short wavelength light emitting devices are amongst the most important devices of compound semiconductors. Rare earth (RE) doping appears as an alternative route to photonic applications. In this work we discuss the role of defects in optical activation and structural properties of ion implanted RE doped ZnO single crystals.